Comparative Corporate Tax Burdens: A Standardized Simulation - Agustin Eka Putri; Dinda Ayuk Saputri; Destyas Rasendriya Aristawati; Salsa Regita Cahyani; Alyssa Risky Khoirunnisa; Fadella Citra Way Elisna; Andika Candra Wijaya (Kampus 5 Universitas Negeri Surabaya, 2025)
This study examines comparative corporate tax burdens in Indonesia, Vietnam, and Brazil through a standardized firm-level simulation model. By employing a consistent financial structure and identical cost assumptions, the analysis estimates each country’s effective tax rate (ETR) and net cash to equity under two different indirect tax treatments: (1) when consumption taxes are creditable and (2) when they are non-creditable and treated as turnover taxes. The findings reveal significant cross-country differences. Vietnam demonstrates the lowest overall ETR, benefiting from moderate corporate income tax (20%) and low dividend withholding tax (5%). Indonesia presents a medium burden due to a 22% corporate income tax and 11% VAT, while Brazil records the highest ETR due to a 34% combined corporate tax rate and an average 12% ICMS turnover tax. The study provides practical insights for multinational firms in choosing investment locations and designing dividend distribution policies, as well as academic implications for comparative tax modeling.